The structural features of Acetobacterium woodii F‐ATP synthase reveal the importance of the unique subunit γ‐loop in Na+ translocation and ATP synthesis - Bogdanović, Nebojša (2020)
The Na+translocating F1FO ATP synthase from Acetobacterium woodii shows a subunit stoichiometry of α3:β3:γ:δ:ε:a:b2:(c2/3)9:c1 and reveals an evolutionary path between synthases and pumps involving adaptations in the rotor c‐ring, which is composed of F‐ and vacuolar‐type c subunits in a stoichiometry of 9 : 1. This hybrid turbine couples rotation with Na+ translocation in the FO part and rotation of the central stalk subunits γ‐ε to drive ATP synthesis in the catalytic α3:β3 headpiece. Here, we isolated a highly pure recombinant A. woodii F‐ATP synthase and present the first projected structure of this hybrid engine as determined by negative‐stain electron microscopy and single‐particle analysis. The uniqueness of the A. woodii F‐ATP synthase is also reflected by an extra 17 amino acid residues loop (195TSGKVKITEETKEEKSK211) in subunit γ. Deleting the loop‐encoding DNA sequence (γΔ195–211) and purifying the recombinant F‐ATP synthase γΔ195–211 mutant provided a platform to study its effect in enzyme stability and activity. The recombinant F‐ATP synthase γΔ195–211 mutant revealed the same subunit composition as the wild‐type enzyme and a minor reduction in ATP hydrolysis. When reconstituted into proteoliposomes ATP synthesis and Na+ transport were diminished, demonstrating the importance of the γ195–211 loop in both enzymatic processes. Based on a structural model, a coupling mechanism for this enzyme is proposed, highlighting the role of the γ‐loop. Finally, the γ195–211 loop of A. woodii is discussed in comparison with the extra γ‐loops of mycobacterial and chloroplasts F‐ATP synthases described to be involved in species‐specific regulatory mechanisms.